2005
DOI: 10.1161/circulationaha.105.542340
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-Generated Oxidants Modulate Left Ventricular Remodeling but Not Infarct Size After Myocardial Infarction

Abstract: Background-Inflammation after myocardial infarction (MI) heralds worse left ventricular (LV) function and clinicaloutcomes. However, whether inflammation affects LV function by extending myonecrosis and/or altering LV remodeling remains unknown. We hypothesized that cytotoxic aldehydes generated during oxidative stress may adversely affect remodeling and infarct size. One theoretical source of reactive aldehydes is oxidation of common ␣-amino acids by myeloperoxidase (MPO) released by leukocytes. However, a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 41 publications
6
130
1
2
Order By: Relevance
“…Moreover, the observed increase in apoptosis in Mpo Ϫ/Ϫ mice is similar to the rise of apoptosis in WT animals during this early phase of reperfusion. Similarly, studies by Vasilyev and colleagues 19 could not show a significant contribution for MPO or its derived oxidants in the induction of apoptosis and necrosis in vivo. MPO rather adversely influenced organ function by the production of cytotoxic aldehydes 19 or the oxidative inactivation of plasminogen activator inhibitor 1 (PAI-1).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, the observed increase in apoptosis in Mpo Ϫ/Ϫ mice is similar to the rise of apoptosis in WT animals during this early phase of reperfusion. Similarly, studies by Vasilyev and colleagues 19 could not show a significant contribution for MPO or its derived oxidants in the induction of apoptosis and necrosis in vivo. MPO rather adversely influenced organ function by the production of cytotoxic aldehydes 19 or the oxidative inactivation of plasminogen activator inhibitor 1 (PAI-1).…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, studies by Vasilyev and colleagues 19 could not show a significant contribution for MPO or its derived oxidants in the induction of apoptosis and necrosis in vivo. MPO rather adversely influenced organ function by the production of cytotoxic aldehydes 19 or the oxidative inactivation of plasminogen activator inhibitor 1 (PAI-1). 39 The present data indeed suggest that MPO has no significant in vivo role in the induction of renal cell death throughout the first moments of I/R but rather has a profound effect on organ function during late reperfusion, known as progression phase.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Treatment of threonine with HOCl also generated acrolein and 2-hydroxypropanal. In a murine model of acute myocardial infarction, myeloperoxidase was found to be a major enzymatic source of acrolein, as demonstrated by a dramatic increase of acrolein in ischemic cardiac tissue obtained from wild-type mice as compared to myeloperoxi-dase-deficient (MPO null) mice [48]. The authors also observed that the MPO-null mice showed better cardiac function 24 days after the ischemic injury.…”
Section: Threonine-threonine Has Been Identified As An Endogenous Soumentioning
confidence: 94%
“…Myeloperoxidase (MPO) -enzyme released from activated neutrophils and monocytes during inflammation -is involved in the promotion of atherosclerosis, the destabilization of atherosclerotic plaque and the pathogenesis of ACS (Nicholls et al, 2005;Tsimikas et al, 2006;Ndrepepa et al, 2011). MPO deposition has been shown in a murine model of acute myocardial infarction (AMI) to be increased near the sites of myocardial rupture (Vasilyev et al, 2005). MPO is one of the important elements in the generation of oxidative stress and the pro-inflammatory stage progress (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%